An evaluation of organic matter dispersed in the Menilite Formation in Silesian Nappe (Polish Outer Carpathians): an optical microscopic approach - Waliczek, Marta; Machowski, Grzegorz; Solecki, Marek Leszek; Stefaniuk, Michał (Geology, Geophysics and Environment, 2022)
In this study, optical microscopic analyses were applied to evaluate the thermal maturity, characteristics of solid bitumen, and other organic matter finely dispersed in Oligocene shales of the Menilite Formation in the Iwonicz-Zdrój–Rudawka Rymanowska Fold (IRF) and Bóbrka–Rogi Fold (BRF) of the Central Carpathian Synclinorium of the Silesian Nappe, Outer Carpathians, Poland. The investigation was carried out at two-unit depths of the shallow and deeper D-1 sections (430 m – IRF and 4,300 m – BRF) and outcrop samples (BRF). The mean random huminite reflectance values indicate immature conditions with respect to hydrocarbon generation in samples from the D-1 shallow section (VRo≈0.40%) and in the outcrop samples (VRo=0.36%). The degree of thermal maturity of the organic matter from a depth of about 4,300 m – BRF based on random vitrinite (VRo≈0.80%) and solid bitumen (BRo≈0.65%) reflectance measurements is associated with the “oil window” for petroleum generation. The organic components dispersed in the examined Menilite Formation samples are typical for hydrocarbon-prone organic matter, suggesting the dominant kerogen type II. The potential precursor maceral for solid bitumen occurring in the examined samples from the deeper D-1 sections is largely the alginite maceral.